Healthcare Professionals’ Acceptance of Digital Cognitive Rehabilitation - van der Ham, Ineke J. M.; van der Vaart, Rosalie; Miedema, Anouk; Visser-Meily, Johanna M. A.; van der Kuil, Milan N. A. (Frontiers in Psychology, 2020)
With technological possibilities in healthcare steadily increasing, more tools for digital cognitive rehabilitation become available. Acceptance of such technological advances is crucial for successful implementation. Therefore, we examined technology acceptance specifically for this form of rehabilitation, in a sample of healthcare providers involved in cognitive rehabilitation. An adjusted version of the Technology Acceptance Model questionnaire was used, including the subscales for perceived usefulness, perceived ease of use, subjective norm ( towards use), and intention to use, which all contribute to actual use of a specific technology. Results indicate a generally favorable attitude towards the use of digital cognitive rehabilitation, and positive responses towards the TAM constructs. Only for subjective norm, a neutral mean response was found, indicating that this could pose a potential obstacle towards implementation. Potential differences between subgroups of different age, gender, and professional background were assessed. Age and gender did not affect the attitude towards digital cognitive rehabilitation. Occupational therapists showed lower scores than healthcare psychologists and physiatrists with regard to perceived usefulness, possibly linked to a difference in operational and managerial tasks. The findings of his study stimulate further implementation of digital cognitive rehabilitation, where the role of subjective norms should be specifically considered.